2015
DOI: 10.17221/233/2014-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

The sulphonylurea herbicide monosulphuron ester sodium as a special male gametocide in Brassica napus L.

Abstract: : The sulphonylurea herbicide monosulphuron ester sodium as a special male gametocide in Brassica napus L. Czech. J. Genet. Plant Breed., 51: 16-22.The sulphonylurea herbicide monosulphuron ester sodium (MES) was first used to induce male sterility in rapeseed (Brassica napus L.). Nearly 100% male sterility was achieved after a single treatment with 10 ml of 0.05-0.10 μg/ml MES solution per plant to the cultivars Zhongshuang No.9 and Zhongshuang No.11 at the uninucleate stage of the longest buds. No adverse ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…It has been confirmed that AHAS should be the target of AHAS-inhibiting herbicides ( Pang et al, 2003 ; Mccourt et al, 2005 , 2006 ). Recently, a few SU-herbicides were found to be excellent CHAs for rapeseed at a lower concentration ( Yu et al, 2006 , 2009 , 2017 ; Cheng et al, 2013 , 2015 ; Yu and He, 2014 ), which attracted many researchers to reveal its underlying mechanism using different approaches ( Cheng et al, 2013 ; Li Z. et al, 2015 ; Zhao et al, 2015 ; Liu et al, 2017 ). Transcriptional and proteomic analyses have identified many differential expression transcripts and proteins in monosulfuron-ester sodium- or amidosulfuron-induced male sterile rapeseed ( Cheng et al, 2013 ; Li Z. et al, 2015 ; Liu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been confirmed that AHAS should be the target of AHAS-inhibiting herbicides ( Pang et al, 2003 ; Mccourt et al, 2005 , 2006 ). Recently, a few SU-herbicides were found to be excellent CHAs for rapeseed at a lower concentration ( Yu et al, 2006 , 2009 , 2017 ; Cheng et al, 2013 , 2015 ; Yu and He, 2014 ), which attracted many researchers to reveal its underlying mechanism using different approaches ( Cheng et al, 2013 ; Li Z. et al, 2015 ; Zhao et al, 2015 ; Liu et al, 2017 ). Transcriptional and proteomic analyses have identified many differential expression transcripts and proteins in monosulfuron-ester sodium- or amidosulfuron-induced male sterile rapeseed ( Cheng et al, 2013 ; Li Z. et al, 2015 ; Liu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some chemicals have been reported as CHAs for hybrid seeds production in rapeseed ( Guan, 2014 ; Yu and He, 2014 ). A few of sulfonylurea herbicides, which are a class of the most widely used acetohydroxyacid synthase (AHAS, EC 2.2.1.6)-inhibiting herbicides, can induce complete male sterility in rapeseed at a concentration less than 1% of that required for their herbicide activity, such as tribenuron methyl (TBM) ( Yu et al, 2006 ; Zhang et al, 2010 ; Yu et al, 2017 ), monosulfuron-ester sodium ( Cheng et al, 2013 , 2015 ; Li Z. et al, 2015 ), and amidosulfuron ( Yu et al, 2009 ). So far, several dozens of commercial rapeseed ( B. napus ) hybrids based on male sterility induced by TBM or other sulfonylurea herbicides have been registered in China ( Cheng et al, 2013 ; Yu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective induction of male sterility using chemical hybridizing agents (CHAs) was first demonstrated in the mid‐20th century (Moore, 1950; Naylor, 1950). To date, numerous chemicals have been evaluated for their applicability as CHAs in different crop species (Chakraborty & Devakumar, 2006a; Kajal Chakraborty & C Devakumar, 2006; Zhang et al., 2017) and some crop specific chemicals are also identified for cotton ( Gossypium hirsutum L.) and Brassica s (Cheng et al., 2015; Ladyman et al., 1990). Unfortunately, most of the evaluated CHAs reduce female fertility, and show varying levels of phytotoxicity ranging from plant growth inhibition and/or reduced seed set (McRae, 1985; Sharma & Sharma, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…AHAS activity requires three cofactors: thiamine diphosphate (ThDP), magnesium ion (Mg 2+ ), and flavin adenine dinucleotide (FAD). Recently, Chinese scientists have demonstrated that some AHAS inhibitors, such as tribenuron-methyl (TBM), amidosulfuron, monosulfuron ester sodium (MES), and SX-1 could act as effective male gametocides when applied at very low doses in B. napus ( Cheng et al 2013 , 2015 , Li et al 2015 , Ning et al 2018 , Yu et al 2006 , 2009 ). Furthermore, male sterility induced by SX-1 in B. napus was analyzed using a multi-omics integrative analysis, and the initial deficiency of protein processing in the endoplasmic reticulum and flavonoid biosynthesis were proposed as the main reasons for its effectiveness ( Ning et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%